Florence remembers Margherita Hack on the 100th anniversary of her birth - Gasperini, Antonella; Strano, Giorgio (Il Colle di Galileo, 2024)
In June 2022, to mark the 100th anniversary of Margherita Hack’s birth, Arcetri Observatory and the Museo Galileo organised a dual event to commemorate the Florentine scientist. Scholars from different disciplinary backgrounds questioned the many facets of Margherita Hack’s life and career, along with her cultural legacy.